Reducing the radiation exposure from CT scanning in children with shunts: a nationwide survey and a departmental CT protocol. (3rd September 2018) - Solth, Anna; Mukerji, Nitin; Strachan, Roger
Abstract: Introduction: Low dose ionising radiation such as from CT scans carries a low but cumulative risk of cancer and children are particularly sensitive. Children with VP Shunts often undergo multiple CT scans. We developed a CT protocol with reduced radiation for paediatric patients with shunts and compared it with the current practice in the other neurosurgical units in the UK and ROI by conducting a nationwide survey. Methods: An email questionnaire was send to the superintendent radiographer in every Neurosurgical unit in the UK and the ROI. Results: The response rate was 70%. Only 5 (19%) of the responding units used a dedicated CT shunt protocol with reduced radiation. Radiation was reduced by lowering the tube current. In comparison, our protocol uses a combination of less tube current and fewer slices. This reduced the radiation exposure of a CT head significantly with sufficient image quality to make a diagnosis. Conclusion: Radiation from CT for paediatric shunt patients scans can and should be reduced. This can be achieved by using reduced radiation protocols. A national paediatric CT shunt protocol could lead to significant reduction in effective radiation dose.